Zinc-based metal organic framework material as well as preparation method and application thereof

By adding cationic surfactant to the preparation of zinc-based metal organic framework materials and adjusting pH, the problems of complex process, time-consuming and high environmental protection costs in the prior art are solved, and the adsorption performance of the material is improved and the process is simplified. and environmentally friendly.

CN119431809AActive Publication Date: 2025-02-14PETROCHINA CO LTD

Patent Information

Application Number
CN202310987080.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-08-07
Publication Date
2025-02-14
Estimated Expiration
2043-08-07

AI Technical Summary

Technical Problem

The existing metal organic framework materials have complex process, long time consumption and the use of organic solvents, which lead to high environmental protection costs, making it difficult to develop high-performance materials with better adsorption performance and lower desorption energy consumption.

Method used

By adding cationic surfactants, such as quaternary ammonium cationic surfactants when preparing zinc-based metal organic framework materials, the pH value of the system is adjusted, and the target solution is obtained through hydrothermal crystallization reaction, and finally washed, suction filtration and activation are carried out. , Zn-MOF material with larger grain size and higher adsorption properties was obtained.

Benefits of technology

The adsorption performance of zinc-based metal organic framework materials has been significantly improved, and the time for completely separating ethylene and ethane has been extended from 5 minutes to 9 minutes, and the process is simple, environmentally friendly and low cost.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119431809A_ABST
    Figure CN119431809A_ABST
Patent Text Reader

Abstract

The invention provides a zinc-based metal organic framework material and a preparation method and application thereof.The preparation method comprises the steps that 3-amino-1, 2, 4-triazole, basic zinc carbonate, methyl alcohol and a phosphoric acid solution are mixed to be uniform, and an alkaline reagent is used for adjusting the pH value of a system to obtain mother liquor; wherein the molar ratio of the basic zinc carbonate to the 3-amino-1, 2, 4-triazole is (1: 10)-(1: 30); adding a cationic surface active agent into the mother solution, uniformly mixing, standing, aging, and carrying out hydrothermal crystallization reaction to obtain a target solution; wherein the molar ratio of the cationic surface active agent to the basic zinc carbonate is (1: 1)-(10: 1); the target solution is washed, subjected to suction filtration and activated, and the zinc-based metal organic framework material is obtained. The preparation method disclosed by the invention is simple and convenient to operate, simple in process, green, environment-friendly and low in production cost, and the adsorption performance of the prepared zinc-based metal organic framework material can be greatly improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a zinc-based metal organic framework material and a preparation method and application thereof, belonging to the technical field of metal organic framework material adsorption and separation. Background Art

[0002] Ethylene is an important basic raw material for petrochemical industry and can be used to manufacture various high-value chemical products. At present, the main sources of ethylene are steam cracking and ethane dehydrogenation, but the products obtained by steam cracking and ethane dehydrogenation inevitably contain some ethane impurities, which need to be further purified to obtain polymerization-grade ethylene. In addition, among the various methods of separating ethylene and ethane, adsorption separation technology has attracted extensive attention from researchers due to its low energy consumption, small investment, simple equipment and high degree of automation.

[0003] The core of adsorption separation is the adsorbent. Metal organic framework materials (MOFs) have large specific surface area and adjustable pore structure properties, and have broad application prospects in the field of adsorption separation. With the continuous development of technology, the requirements for MOFs materials are further improved, and there is an urgent need to develop high-performance MOFs materials with better adsorption performance and lower desorption energy consumption. However, the development of a new MOFs structure has the problems of long R&D cycle and high R&D investment. Therefore, modifying the existing MOFs structure to improve its adsorption performance is a more efficient and convenient method.

[0004] CN110314653A discloses a preparation and application of a high-stability monovalent copper modified metal organic framework material, which adopts one or more methods in vapor deposition, spray drying and initiated polymerization, and applies a hydrophobic coating to the surface of the monovalent copper modified metal organic framework material to improve the moisture resistance of the monovalent copper modified metal organic framework material, thereby significantly improving the stability of monovalent copper. The high-stability monovalent copper modified metal organic framework material has a good application effect in fuel oil desulfurization, olefin alkane separation and carbon monoxide recovery. The disadvantage of this preparation method is that the process is relatively complicated and takes a long time.

[0005] CN109734957A discloses a method for preparing a modified metal organic framework material and the obtained material, wherein the preparation method comprises: washing and solvent exchanging the synthesized MOF material, and then performing pore modification to obtain a MOFs material with good separation performance for methane. The specific operation of pore modification is as follows: placing the dried MOFs powder and imidazole together in dehydrated dichloromethane, stirring at 80°C for 24 hours under anhydrous and oxygen-free nitrogen protection conditions, and then performing vacuum high-temperature treatment to obtain the modified MOFs material. The disadvantage of this method is that the operating conditions are anhydrous and oxygen-free conditions, which are relatively harsh, and the use of dichloromethane increases the amount of organic solvent used, which is not only not environmentally friendly, but also greatly increases the synthesis cost of modified MOFs.

[0006] Therefore, providing a new type of zinc-based metal organic framework material and its preparation method and application has become a technical problem that needs to be solved urgently in this field. Summary of the invention

[0007] In order to solve the above-mentioned shortcomings and deficiencies, the object of the present invention is to provide a zinc-based metal organic framework material and a preparation method and application thereof.

[0008] In order to achieve the above objectives, on the one hand, the present invention provides a method for preparing a zinc-based metal organic framework material, wherein the preparation method comprises:

[0009] Step 1: uniformly mix 3-amino-1,2,4-triazole, basic zinc carbonate, methanol and phosphoric acid solution, and adjust the pH value of the system with an alkaline reagent to obtain a mother liquor; wherein the molar ratio of basic zinc carbonate to 3-amino-1,2,4-triazole is 1:10-1:30;

[0010] Step 2: adding the cationic surfactant to the mother liquor and mixing them evenly, and performing a hydrothermal crystallization reaction after standing and aging to obtain a target solution; wherein the molar ratio of the cationic surfactant to basic zinc carbonate is 1:1-10:1;

[0011] Step three: washing, filtering and activating the target solution to obtain the zinc-based metal organic framework material.

[0012] As a specific embodiment of the preparation method described above of the present invention, in step 1, phosphoric acid, water and methanol are first prepared into a phosphoric acid solution, and then basic zinc carbonate and 3-amino-1,2,4-triazole are added to the prepared phosphoric acid solution, mechanical stirring is performed to mix the reactants evenly, and ammonia water is used to adjust the pH value of the system to obtain a mother liquor.

[0013] As a specific embodiment of the above preparation method of the present invention, in step 1, the molar ratio of basic zinc carbonate to 3-amino-1,2,4-triazole is 1:20-1:25.

[0014] As a specific embodiment of the preparation method described above of the present invention, wherein, in step 1, in the phosphoric acid solution, the molar ratio of phosphoric acid to water is 1:100-1:700, preferably 1:300-1:350, and more preferably 1:310.

[0015] As a specific embodiment of the preparation method described above of the present invention, in step 1, the mixing is uniformly carried out by ultrasonic or mechanical stirring for 10-120 minutes.

[0016] As a specific embodiment of the preparation method described above of the present invention, in step 1, an alkaline reagent is used to adjust the pH value of the system to 8-10.

[0017] As a specific embodiment of the preparation method described above in the present invention, in step 1, the alkaline reagent includes one or a combination of sodium hydroxide, potassium hydroxide, calcium hydroxide, ammonia water, etc.

[0018] As a specific embodiment of the preparation method described above of the present invention, in step 2, the molar ratio of the cationic surfactant to basic zinc carbonate is 3:1-4:1.

[0019] As a specific embodiment of the above preparation method of the present invention, in step 2, the cationic surfactant is a quaternary ammonium salt cationic surfactant.

[0020] As a specific embodiment of the preparation method described above of the present invention, the quaternary ammonium salt cationic surfactant includes one or a combination of long-chain alkyl dimethyl benzyl ammonium bromide, hexadecyl trimethyl ammonium chloride, octadecyl trimethyl ammonium chloride, hexadecyl trimethyl ammonium bromide (CTAB), octadecyl trimethyl ammonium bromide, hexadecyl dimethyl hydroxyethyl ammonium chloride, etc.

[0021] As a specific embodiment of the above preparation method of the present invention, the long-chain alkyl dimethyl benzyl ammonium bromide includes dodecyl dimethyl benzyl ammonium bromide, hexadecyl dimethyl benzyl ammonium bromide and octadecyl dimethyl benzyl ammonium bromide.

[0022] The present invention adds a cationic surfactant, such as a quaternary ammonium salt cationic surfactant such as hexadecyl dimethyl benzyl ammonium bromide, when preparing a zinc-based metal organic framework material. The cationic surfactant exists in the form of a cation in the solution, and has a positively charged head and a hydrophobic tail. After the 3-amino-1,2,4-triazole ligand is deprotonated, the ligand exists as a negatively charged group. The negatively charged group is surrounded by the cation to form an orderly hydrophobic film on the outer surface. Due to the presence of the hydrophobic film, the weak hydrophobic interaction between the cationic surfactant and the surface of the crystal core can more effectively inhibit agglomeration and make the crystal core more evenly dispersed. At the same time, due to the slow release of 3-amino-1,2,4-triazole in the reaction solution, the nucleation rate is slowed down, so that larger grains can be obtained, which can improve the separation performance of the prepared Zn-MOF for ethylene and ethane. In addition, since quaternary ammonium cationic surfactants and phosphoric acid are used in the preparation process, the obtained Zn-MOF pores have abundant phosphoric acid and amino groups, and these groups have a higher affinity for ethylene, which can further improve the separation performance of Zn-MOF for ethylene and ethane.

[0023] As a specific embodiment of the preparation method described above of the present invention, in step 2, the uniform mixing can be achieved by ultrasonic or mechanical stirring, and the time of ultrasonic or mechanical stirring can be reasonably adjusted according to the actual operation needs on site.

[0024] As a specific implementation of the above preparation method of the present invention, in step 2, the static aging time is 20 minutes to 6 hours.

[0025] As a specific embodiment of the preparation method described above in the present invention, in step 2, the temperature of the hydrothermal crystallization reaction is 60-200° C. and the time is 2-48 hours.

[0026] As a specific embodiment of the preparation method described above of the present invention, in step three, the activation comprises: vacuum drying the solid product obtained by filtration at 60-150° C. for 6-24 hours.

[0027] In step 3 of the preparation method described above, washing and filtration are conventional operations, which can be reasonably operated according to the actual needs of the on-site operation and the solvent used for washing and the number of washing times can be reasonably adjusted. For example, in some embodiments of the present invention, the solvent used for washing is deionized water, and the number of washing times is 3-5 times.

[0028] On the other hand, the present invention also provides a zinc-based metal organic framework material / zinc-based microporous metal organic framework material, wherein the zinc-based metal organic framework material is prepared by the above-mentioned method for preparing the zinc-based metal organic framework material.

[0029] On the other hand, the present invention also provides the use of the above-mentioned zinc-based metal organic framework material in the adsorption and separation of light hydrocarbons or CO2 and N2.

[0030] As a specific implementation of the above application of the present invention, the low-carbon hydrocarbons include ethylene and ethane.

[0031] Compared with the prior art, the beneficial technical effects that can be achieved by the present invention include:

[0032] The present invention adds a cationic surfactant, such as a quaternary ammonium salt cationic surfactant, when preparing a zinc-based metal organic framework material, which can significantly improve the adsorption performance of the prepared zinc-based metal organic framework material. The zinc-based metal organic framework material is used for adsorption and separation of ethylene and ethane. Compared with the existing zinc-based metal organic framework material, under the same adsorption and separation conditions, the time for complete separation is increased from 5 minutes to 9 minutes.

[0033] The preparation method of the zinc-based metal organic framework material provided by the present invention is easy to operate, simple in process, saves process flow and time; does not require the use of additional organic solvents, is more environmentally friendly; and the cationic surfactant used is inexpensive, thereby reducing production costs. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0035] Figure 1 In the characterization test example 1 of the present invention, the XRD patterns obtained by performing XRD analysis on the Zn-MOF provided in Examples 1 to 3 and Comparative Example 1 are shown.

[0036] Figure 2a This is a scanning electron microscope image (10 μm) obtained by performing electron microscope characterization on the Zn-MOF provided in Comparative Example 1 in Characterization Test Example 2 of the present invention.

[0037] Figure 2b This is a scanning electron microscope image (2 μm) obtained by performing electron microscope characterization on the Zn-MOF provided in Comparative Example 1 in Characterization Test Example 2 of the present invention.

[0038] Figure 2c This is a scanning electron microscope image (20 μm) obtained by performing electron microscope characterization on the Zn-MOF provided in Example 1 in Characterization Test Example 2 of the present invention.

[0039] Figure 2dThis is a scanning electron microscope image (2 μm) obtained by performing electron microscope characterization on the Zn-MOF provided in Example 1 in Characterization Test Example 2 of the present invention.

[0040] Figure 3 This is the fixed bed breakthrough curve of Zn-MOF provided in Comparative Example 1 in Performance Test Example 1 of the present invention.

[0041] Figure 4 This is the fixed bed breakthrough curve of Zn-MOF provided in Example 1 of Performance Test Example 1 of the present invention.

[0042] Figure 5 This is the fixed bed breakthrough curve of Zn-MOF provided in Comparative Example 2 in Performance Test Example 1 of the present invention.

[0043] Figure 6 This is the fixed bed breakthrough curve of Zn-MOF provided in Comparative Example 3 in Performance Test Example 1 of the present invention. DETAILED DESCRIPTION

[0044] It should be noted that the term "comprises" and any variations thereof in the specification and claims of the present invention and the above-mentioned drawings are intended to cover non-exclusive inclusions. For example, a process, method, technique, system, product or equipment that includes a series of steps or units is not necessarily limited to those steps or units clearly listed, but may include other steps or units that are not clearly listed or inherent to these processes, methods, techniques, products or equipment.

[0045] "Scope" disclosed in the present invention is given in the form of lower limit and upper limit. It can be one or more lower limits, and one or more upper limits respectively. A given range is defined by selecting a lower limit and an upper limit. The selected lower limit and upper limit define the boundaries of a particular range. All ranges defined in this way are combinable, i.e. any lower limit can be combined with any upper limit to form a range. For example, for a specific parameter, a range of 60-120 and 80-110 is listed, and it is understood that a range of 60-110 and 80-120 is also expected. In addition, if the minimum range values ​​listed are 1 and 2, and the maximum range values ​​listed are 3, 4 and 5, then the following ranges can all be expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5.

[0046] In the present invention, unless otherwise specified, the numerical range "ab" represents an abbreviation of any real number combination between a and b, where a and b are real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" have been listed in the present invention, and "0-5" is just an abbreviation of these numerical combinations.

[0047] In the present invention, unless otherwise specified, all embodiments and preferred embodiments mentioned in the present invention can be combined with each other to form a new technical solution.

[0048] In the present invention, unless otherwise specified, all technical features and preferred features mentioned in the present invention can be combined with each other to form a new technical solution.

[0049] In the present invention, unless otherwise specified, all steps mentioned herein may be performed sequentially or randomly, but are preferably performed sequentially. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), which means that step (c) may be added to the method in any order, for example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.

[0050] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention is further described in detail below in conjunction with the attached table, drawings and examples. The following described embodiments are some embodiments of the present invention, rather than all embodiments, and are only used to illustrate the present invention, and should not be regarded as limiting the scope of the present invention. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in the field without making creative work are within the scope of protection of the present invention. If the specific conditions are not specified in the embodiments, they are carried out according to the normal conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified in the reagents or instruments used, they are all conventional products that can be purchased commercially.

[0051] Example 1

[0052] This embodiment provides a zinc-based metal organic framework material, which is prepared by a preparation method comprising the following specific steps:

[0053] Step (1): weigh 0.42 g of phosphoric acid, 26 g of water and 10.92 g of methanol to prepare a phosphoric acid solution;

[0054] Step (2): 1.2 g of basic zinc carbonate (molecular formula: 3Zn(OH)2·2ZnCO3, molecular weight: 548.92) and 3.6 g of 3-amino-1,2,4-triazole (molecular weight: 84) (the molar ratio of basic zinc carbonate to 3-amino-1,2,4-triazole is 1:20) are added to the above-prepared phosphoric acid solution, mechanically stirred for 0.5 h to mix the reactants evenly, and ammonia water is used to adjust the pH value of the system to 8-9 to obtain a mixture A;

[0055] Step (3): adding 2.9 g of CTAB (relative molecular weight 364) to mixture A, continuing stirring for 0.5 h, standing at room temperature for 20 minutes after stirring, then transferring the mixture to a homogeneous reactor, performing hydrothermal crystallization reaction at 180° C. for 24 h, cooling to room temperature after the reaction was completed, and obtaining mixture B;

[0056] Step (4) Rinse the mixture B with 30-50 mL of deionized water for 3-5 times. After washing, filter the mixture using a suction filtration device. Activate the obtained filter cake in a vacuum drying oven at 100° C. for 12 h to obtain 1.98 g of Zn-MOF.

[0057] Example 2

[0058] This embodiment provides a zinc-based metal organic framework material, which is prepared by a preparation method comprising the following specific steps:

[0059] Step (1): Weigh 1.26 g of phosphoric acid, 26 g of water and 10.92 g of methanol to prepare a phosphoric acid solution;

[0060] Step (2): 1.8 g of basic zinc carbonate (molecular formula: 3Zn(OH)2·2ZnCO3, molecular weight: 548.92) and 3.6 g of 3-amino-1,2,4-triazole (the molar ratio of basic zinc carbonate to 3-amino-1,2,4-triazole is 1:13) are added to the above-prepared phosphoric acid solution, mechanically stirred for 0.5 h to mix the reactants evenly, and ammonia water is used to adjust the pH value of the system to 9 to obtain a mixture A;

[0061] Step (3): 1.46 g of CTAB was added to the mixture A, and the mixture was stirred for 1 h. After the stirring was completed, the mixture was allowed to stand at room temperature for 60 minutes. The mixture was then transferred to a homogeneous reactor and subjected to a hydrothermal crystallization reaction at 150° C. for 48 h. After the reaction was completed, the mixture was cooled to room temperature to obtain a mixture B.

[0062] Step (4): Rinse the mixture B with 30-50 mL of deionized water for 3-5 times. After washing, filter the mixture using a suction filtration device. Activate the obtained filter cake in a vacuum drying oven at 100° C. for 12 h to obtain 2.01 g of Zn-MOF.

[0063] Embodiment 3:

[0064] This embodiment provides a zinc-based metal organic framework material, which is prepared by a preparation method comprising the following specific steps:

[0065] Step (1): weigh 0.21 g of phosphoric acid, 26 g of water and 10.92 g of methanol to prepare a phosphoric acid solution;

[0066] Step (2): 0.9 g of basic zinc carbonate (molecular formula: 3Zn(OH)2·2ZnCO3, molecular weight: 548.92) and 3.6 g of 3-amino-1,2,4-triazole (the molar ratio of basic zinc carbonate to 3-amino-1,2,4-triazole is 1:26) are added to the above-prepared phosphoric acid solution, mechanically stirred for 0.5 h to mix the reactants evenly, and calcium hydroxide is used to adjust the pH value of the system to 9 to obtain a mixture A;

[0067] Step (3): adding 5.98 g of CTAB to mixture A, continuing stirring for 2 h, standing at room temperature for 6 h after stirring, then transferring the mixture to a homogeneous reactor, performing hydrothermal crystallization reaction at 120° C. for 48 h, cooling to room temperature after the reaction, and obtaining mixture B;

[0068] Step (4): Rinse the mixture B with 30-50 mL of deionized water for 3-5 times. After washing, filter the mixture using a suction filtration device. Activate the obtained filter cake in a vacuum drying oven at 100° C. for 12 h to obtain 1.83 g of Zn-MOF.

[0069] Example 4

[0070] This embodiment provides a zinc-based metal organic framework material, which is prepared by a preparation method comprising the following specific steps:

[0071] Step (1): weigh 0.6 g of phosphoric acid, 26 g of water and 10.92 g of methanol to prepare a phosphoric acid solution;

[0072] Step (2): 1.3 g of basic zinc carbonate (molecular formula: 3Zn(OH)2·2ZnCO3, molecular weight: 548.92) and 5.58 g of 3-amino-1,2,4-triazole (the molar ratio of basic zinc carbonate to 3-amino-1,2,4-triazole is 1:28) are added to the above-prepared phosphoric acid solution, mechanically stirred for 1 hour to mix the reactants evenly, and ammonia water is used to adjust the pH value of the system to 8.5 to obtain a mixture A;

[0073] Step (3): adding 4.5 g of dodecyldimethylbenzylammonium bromide to mixture A, continuing stirring for 1.5 h, standing at room temperature for 1 h after stirring, then transferring the mixture to a homogeneous reactor, performing hydrothermal crystallization reaction at 170° C. for 36 h, cooling to room temperature after the reaction, and obtaining mixture B;

[0074] Step (4): Rinse the mixture B with 30-50 mL of deionized water for 3-5 times. After washing, filter the mixture using a suction filtration device. Activate the obtained filter cake in a vacuum drying oven at 120° C. for 8 h to obtain 2.1 g of Zn-MOF.

[0075] Example 5

[0076] This embodiment provides a zinc-based metal organic framework material, which is prepared by a preparation method comprising the following specific steps:

[0077] Step (1): weigh 0.6 g of phosphoric acid, 26 g of water and 10.92 g of methanol to prepare a phosphoric acid solution;

[0078] Step (2): adding 0.9 g of basic zinc carbonate (molecular formula: 3Zn(OH)2·2ZnCO3, molecular weight: 548.92) and 2.07 g of 3-amino-1,2,4-triazole (the molar ratio of basic zinc carbonate to 3-amino-1,2,4-triazole is 1:15) to the above-prepared phosphoric acid solution, mechanically stirring for 1 hour to mix the reactants evenly, and adjusting the pH value of the system to 9.5 with sodium hydroxide to obtain a mixture A;

[0079] Step (3): 1.7 g of octadecyltrimethylammonium chloride was added to the mixture A, and the mixture was stirred for 1.5 h. After the stirring was completed, the mixture was allowed to stand at room temperature for 1 h. The mixture was then transferred to a homogeneous reactor and subjected to a hydrothermal crystallization reaction at 160° C. for 20 h. After the reaction was completed, the mixture was cooled to room temperature to obtain a mixture B.

[0080] Step (4): Rinse the mixture B with 30-50 mL of deionized water for 3-5 times. After washing, filter the mixture using a suction filtration device. Activate the obtained filter cake in a vacuum drying oven at 130° C. for 6 h to obtain 1.44 g of Zn-MOF.

[0081] Example 6

[0082] This embodiment provides a zinc-based metal organic framework material, which is prepared by a preparation method comprising the following specific steps:

[0083] Step (1): weigh 0.42 g of phosphoric acid, 26 g of water and 10.92 g of methanol to prepare a phosphoric acid solution;

[0084] Step (2): 0.94 g of basic zinc carbonate (molecular formula: 3Zn(OH)2·2ZnCO3, molecular weight: 548.92) and 3.6 g of 3-amino-1,2,4-triazole (molecular weight: 84) (the molar ratio of basic zinc carbonate to 3-amino-1,2,4-triazole is 1:25) are added to the above-prepared phosphoric acid solution, mechanically stirred for 0.5 h to mix the reactants evenly, and sodium hydroxide is used to adjust the pH value of the system to 8.5 to obtain a mixture A;

[0085] Step (3): 3.2 g of CTAB (relative molecular weight 364) was added to the mixture A, and the mixture was stirred for 0.5 h. After the stirring was completed, the mixture was allowed to stand at room temperature for 30 minutes, and then the mixture was transferred to a homogeneous reactor and subjected to hydrothermal crystallization reaction at 190° C. for 18 h. After the reaction was completed, the mixture was cooled to room temperature to obtain a mixture B;

[0086] Step (4) Rinse the mixture B with 30-50 mL of deionized water for 3-5 times. After washing, filter the mixture using a suction filtration device. Activate the obtained filter cake in a vacuum drying oven at 120° C. for 8 h to obtain 1.27 g of Zn-MOF.

[0087] Example 7

[0088] This embodiment provides a zinc-based metal organic framework material, which is prepared by a preparation method comprising the following specific steps:

[0089] Step (1): weigh 0.42 g of phosphoric acid, 26 g of water and 10.92 g of methanol to prepare a phosphoric acid solution;

[0090] Step (2): 1.19 g of basic zinc carbonate (molecular formula: 3Zn(OH)2·2ZnCO3, molecular weight: 548.92) and 4.2 g of 3-amino-1,2,4-triazole (molecular weight: 84) (the molar ratio of basic zinc carbonate to 3-amino-1,2,4-triazole is 1:23) are added to the above-prepared phosphoric acid solution, mechanically stirred for 0.5 h to mix the reactants evenly, and potassium hydroxide is used to adjust the pH value of the system to 9 to obtain a mixture A;

[0091] Step (3): 3.2 g of CTAB (relative molecular weight 364) was added to the mixture A, and the mixture was stirred for 0.5 h. After the stirring was completed, the mixture was allowed to stand at room temperature for 40 minutes, and then the mixture was transferred to a homogeneous reactor and subjected to hydrothermal crystallization reaction at 160° C. for 22 h. After the reaction was completed, the mixture was cooled to room temperature to obtain a mixture B;

[0092] Step (4) Rinse the mixture B with 30-50 mL of deionized water for 3-5 times. After washing, filter the mixture using a suction filtration device. Activate the obtained filter cake in a vacuum drying oven at 150° C. for 6 h to obtain 1.43 g of Zn-MOF.

[0093] Comparative Example 1

[0094] This comparative example provides a zinc-based metal organic framework material, which is prepared by a preparation method comprising the following specific steps:

[0095] Step (1): weigh 0.42 g of phosphoric acid and 26 g and 10.92 g of methanol and water to prepare a phosphoric acid solution;

[0096] Step (2): 1.2 g of basic zinc carbonate (molecular formula: 3Zn(OH)2·2ZnCO3, molecular weight: 548.92) and 3.6 g of 3-amino-1,2,4-triazole (the molar ratio of basic zinc carbonate to 3-amino-1,2,4-triazole is 1:20) are added to the above-prepared phosphoric acid solution, mechanically stirred for 0.5 h to mix the reactants evenly, and ammonia water is used to adjust the pH value of the system to 8-9 to obtain a mixture A;

[0097] Step (3): standing at room temperature for 20 minutes, then transferring the mixture into a homogeneous reactor, performing a hydrothermal crystallization reaction at 180° C. for 24 hours, and cooling to room temperature after the reaction to obtain a mixture B;

[0098] Step (4): Rinse the mixture B with 30-50 mL of deionized water for 3-5 times. After washing, filter the mixture using a suction filtration device. Activate the obtained filter cake in a vacuum drying oven at 100° C. for 12 h to obtain 1.98 g of Zn-MOF.

[0099] Comparative Example 2

[0100] This comparative example provides a zinc-based metal organic framework material, which is prepared by a preparation method comprising the following specific steps:

[0101] Step (1): weigh 0.42 g of phosphoric acid, 26 g of water and 10.92 g of methanol to prepare a phosphoric acid solution;

[0102] Step (2): 1.2 g of basic zinc carbonate (3Zn(OH)2·2ZnCO3, molecular weight 548.92) and 3.6 g of 3-amino-1,2,4-triazole (molecular weight 84) (the molar ratio of basic zinc carbonate to 3-amino-1,2,4-triazole is 1:20) are added to the above-prepared phosphoric acid solution, mechanically stirred for 0.5 h to mix the reactants evenly, and ammonia water is used to adjust the pH value of the system to 8-9 to obtain a mixture A;

[0103] Step (3): adding 0.64 g of CTAB (relative molecular weight 364) to mixture A, continuing stirring for 0.5 h, standing at room temperature for 20 minutes after stirring, then transferring the mixture to a homogeneous reactor, performing a hydrothermal crystallization reaction at 180° C. for 24 h, cooling to room temperature after the reaction is completed, and obtaining a mixture B, wherein the molar ratio of CTAB to basic zinc carbonate is 0.8:1;

[0104] Step (4) Rinse the mixture B with 30-50 mL of deionized water for 3-5 times. After washing, filter the mixture using a suction filtration device. Activate the obtained filter cake in a vacuum drying oven at 100° C. for 12 h to obtain 1.83 g of Zn-MOF.

[0105] Comparative Example 3

[0106] This comparative example provides a zinc-based metal organic framework material, which is prepared by a preparation method comprising the following specific steps:

[0107] Step (1): weigh 0.42 g of phosphoric acid, 26 g of water and 10.92 g of methanol to prepare a phosphoric acid solution;

[0108] Step (2): 1.2 g of basic zinc carbonate (3Zn(OH)2·2ZnCO3, molecular weight 548.92) and 3.6 g of 3-amino-1,2,4-triazole (molecular weight 84) (the molar ratio of basic zinc carbonate to 3-amino-1,2,4-triazole is 1:20) are added to the above-prepared phosphoric acid solution, mechanically stirred for 0.5 h to mix the reactants evenly, and ammonia water is used to adjust the pH value of the system to 8-9 to obtain a mixture A;

[0109] Step (3): adding 8.74 g of CTAB (relative molecular weight 364) to mixture A, continuing stirring for 0.5 h, standing at room temperature for 20 minutes after stirring, and then transferring the mixture to a homogeneous reactor, performing a hydrothermal crystallization reaction at 180° C. for 24 h, cooling to room temperature after the reaction is completed, and obtaining a mixture B, wherein the molar ratio of CTAB to basic zinc carbonate is 11:1;

[0110] Step (4) Rinse the mixture B with 30-50 mL of deionized water for 3-5 times. After washing, filter the mixture using a suction filtration device. Activate the obtained filter cake in a vacuum drying oven at 100° C. for 12 h to obtain 1.90 g of Zn-MOF.

[0111] Characterization Test Example 1

[0112] In this characterization test example, the Zn-MOF provided in Examples 1 to 3 and Comparative Example 1 was subjected to XRD analysis. The XRD analysis was performed using an X-ray powder diffractometer (Bruker D2). The test conditions were: scanning voltage 40 kV, scanning current 30 mA, and test angle 5-50°. The obtained XRD pattern is shown in the figure below: Figure 1 shown.

[0113] from Figure 1 It can be seen that the Zn-MOF prepared in Examples 1 to 3 of the present invention and the Zn-MOF prepared in Comparative Example 1 have the same diffraction peaks, indicating that the addition of CTAB does not change the crystal structure of Zn-MOF.

[0114] Characterization Test Example 2

[0115] In this characterization test example, the Zn-MOF provided in Example 1 and Comparative Example 1 were characterized by electron microscopy. The scanning electron microscope image of the Zn-MOF provided in Comparative Example 1 is shown in FIG. Figure 2a and Figure 2b As shown, the scanning electron microscope image of Zn-MOF provided in Example 1 is as follows Figure 2c and Figure 2d shown.

[0116] from Figure 2a and Figure 2b It can be seen that in Comparative Example 1, the crystal particle size is relatively small, only 17.74 μm, and in Example 1, the crystal particle size is 35.94 μm, which is significantly increased compared with the crystal size of Comparative Example 1.

[0117] Performance Test Example 1

[0118] In this performance test example, the Zn-MOF provided in Example 1 and Comparative Examples 1 to 3 is subjected to fixed bed penetration test, and the specific operation steps include: 1) the sample to be tested is loaded into a sample tube; 2) the sample tube is purged and activated at 100°C for 12 hours under N2 atmosphere; 3) the sample tube is installed on a fixed bed penetration test device (a conventional device used in the art), and the evaluation is carried out according to the following test conditions, which include: test temperature 0°C, test pressure 1 bar, raw material is 50v / 50v ethylene ethane mixture, gas flow rate is 4mL / min, and sample size is 0.8mL.

[0119] The fixed bed breakthrough curve of Zn-MOF provided in Comparative Example 1 is as follows Figure 3 As shown, the fixed bed breakthrough curve of Zn-MOF provided in Example 1 is as follows Figure 4 shown.

[0120] from Figure 3 It can be seen that ethylene penetration was detected after 5 minutes, and the time for ethylene and ethane to be completely separated was about 5 minutes. Figure 4 It can be seen that ethylene can be detected in the exhaust gas after 1 minute, and the complete separation time of ethylene and ethane is about 9 minutes, which shows that compared with the Zn-MOF provided in Comparative Example 1, the Zn-MOF provided in Example 1 of the present invention has better selectivity for ethylene, and it also has better ethylene and ethane adsorption and separation performance.

[0121] The fixed bed breakthrough curve of Zn-MOF provided in Comparative Example 2 is as follows Figure 5 As shown, the fixed bed breakthrough curve of Zn-MOF provided in Comparative Example 3 is as follows Figure 6 shown.

[0122] In Comparative Example 2, the molar ratio of CTAB to basic zinc carbonate is only 0.8:1, which is lower than 1:1 claimed in the present application. Figure 5It can be seen that when the amount of CTAB is too low, the improvement of the ethylene ethane adsorption separation performance of the Zn-MOF material is not obvious; while in Comparative Example 3, the molar ratio of CTAB to basic zinc carbonate is as high as 11:1, which is higher than the 10:1 claimed in the present application. Figure 6 It can be seen that when the amount of CTAB is too high and exceeds the given range, the ethylene ethane adsorption and separation performance of the obtained Zn-MOF is greatly reduced. Figure 3 and Figure 6 It can be seen that the ethylene ethane adsorption separation performance of the Zn-MOF material provided in Comparative Example 3 is even worse than that of the material before modification, that is, the ethylene ethane adsorption separation performance of the Zn-MOF provided in Comparative Example 1. This shows that simply increasing the amount of cationic surfactant cannot further improve the ethylene ethane adsorption separation performance of the Zn-MOF material, and only by controlling the molar ratio of the cationic surfactant to basic zinc carbonate to 1:1-10:1 can the ethylene ethane adsorption separation performance of the obtained Zn-MOF material be significantly improved.

[0123] Compared with the prior art, the zinc-based metal organic framework material provided by the embodiment of the present invention can achieve the following beneficial technical effects:

[0124] In the embodiment of the present invention, cationic surfactants, such as quaternary ammonium salt cationic surfactants, are added when preparing zinc-based metal organic framework materials, which can significantly improve the adsorption performance of the prepared zinc-based metal organic framework materials. The zinc-based metal organic framework materials prepared in the embodiment of the present invention are used for adsorption and separation of ethylene and ethane. Compared with the existing zinc-based metal organic framework materials, under the same adsorption and separation conditions, the time for complete separation is increased from 5 minutes to 9 minutes.

[0125] The preparation method of the zinc-based metal organic framework material provided by the embodiment of the present invention is easy to operate, simple in process, saves process flow and time; does not require the use of additional organic solvents, is more environmentally friendly; and the cationic surfactant used is inexpensive, thereby reducing production costs.

[0126] The above is only a specific embodiment of the present invention, and cannot be used to limit the scope of the invention. Therefore, the replacement of equivalent components, or equivalent changes and modifications made according to the protection scope of the patent of the present invention, should still fall within the scope of this patent. In addition, the technical features of the present invention can be freely combined with each other, with each other and with each other, and with each other.

Claims

1. A method for preparing a zinc-based metal organic framework material, characterized in that: The preparation method comprises: Step 1: uniformly mix 3-amino-1,2,4-triazole, basic zinc carbonate, methanol and phosphoric acid solution, and adjust the pH value of the system with an alkaline reagent to obtain a mother liquor; wherein the molar ratio of basic zinc carbonate to 3-amino-1,2,4-triazole is 1:10-1:30; Step 2: adding the cationic surfactant to the mother liquor and mixing them evenly, and performing a hydrothermal crystallization reaction after standing and aging to obtain a target solution; wherein the molar ratio of the cationic surfactant to basic zinc carbonate is 1:1-10:1; Step three: washing, filtering and activating the target solution to obtain the zinc-based metal organic framework material.

2. The preparation method according to claim 1, characterized in that: In step 1, the molar ratio of basic zinc carbonate to 3-amino-1,2,4-triazole is 1:20-1:

25.

3. The preparation method according to claim 1 or 2, characterized in that: In step 1, in the phosphoric acid solution, the molar ratio of phosphoric acid to water is 1:100-1:

700.

4. The preparation method according to claim 1 or 2, characterized in that: In step 1, the mixture is uniformly mixed by ultrasonic or mechanical stirring for 10-120 minutes.

5. The preparation method according to claim 1 or 2, characterized in that: In step 1, an alkaline reagent is used to adjust the pH value of the system to 8-10.

6. The preparation method according to claim 5, characterized in that: In step 1, the alkaline reagent includes one or a combination of sodium hydroxide, potassium hydroxide, calcium hydroxide, and ammonia water.

7. The preparation method according to claim 1, characterized in that: In step 2, the molar ratio of the cationic surfactant to basic zinc carbonate is 3:1-4:

1.

8. The preparation method according to claim 1 or 7, characterized in that: In step 2, the cationic surfactant is a quaternary ammonium salt cationic surfactant.

9. The preparation method according to claim 8, characterized in that: The quaternary ammonium salt cationic surfactant includes one or a combination of long-chain alkyl dimethyl benzyl ammonium bromide, hexadecyl trimethyl ammonium chloride, octadecyl trimethyl ammonium chloride, hexadecyl trimethyl ammonium bromide, octadecyl trimethyl ammonium bromide, and hexadecyl dimethyl hydroxyethyl ammonium chloride.

10. The preparation method according to claim 1 or 7, characterized in that: In step 2, the static aging time is 20 minutes to 6 hours.

11. The preparation method according to claim 1 or 7, characterized in that: In step 2, the temperature of the hydrothermal crystallization reaction is 60-200° C. and the time is 2-48 hours.

12. The preparation method according to claim 1 or 7, characterized in that: In step three, the activation comprises: vacuum drying the solid product obtained by filtration at 60-150° C. for 6-24 hours.

13. A zinc-based metal organic framework material, characterized in that: The zinc-based metal organic framework material is prepared by the preparation method of the zinc-based metal organic framework material according to any one of claims 1 to 12.

14. Use of the zinc-based metal organic framework material according to claim 13 in the adsorption and separation of light hydrocarbons or CO2 and N2.

15. The use according to claim 14, characterized in that: The light hydrocarbons include ethylene and ethane.

Citation Information

Patent Citations

  • Preparation method of modified metal-organic framework material and material prepared by same

    CN109734957A

  • Preparation and application of high-stability cuprous modified metal organic framework material

    CN110314653A

  • Method for regulating ZIF-8 crystal morphology by utilizing surfactant

    CN107722046A

  • Preparation method of modified metal organic framework material for adsorbing and separating BTEX in C8 aromatic hydrocarbon

    CN113441111A

  • Synthesis method of zinc-based microporous metal organic framework material and application of material

    CN115558117A

Cited By

  • Application of zinc-based microporous metal organic framework material in formaldehyde removal

    CN120132811A

  • Seawater-corrosion-resistant ultrafiltration membrane for water treatment and preparation method thereof

    CN121060338A